Dynamics of perennial halophytic communities in the Salicornioideae sufamily: a case study from the Tinto river and western Iberian peninsula - Ramírez Chueca, Esteban; Rufo, Lourdes; de la Fuente, Vicenta (Mediterranean Botany, 2025)
This study investigates perennial halophyte vegetation communities within the Salicornioideae subfamily in the marshlands of the southwestern Iberian Peninsula, with a particular emphasis on the Tinto River salt marshes. We focus on communities dominated by three Sarcocornia species (S. perennis, S. pruinosa, and S. alpini) and Arthrocnemum macrostachyum. Utilizing geobotanical analysis, we reaffirm existing classifications, delineating one association for A. macrostachyum (Inulo crithmoidis-Arthrocnemetum macrostachyi) and three for Sarcocornia (Puccinellio ibericae-Sarcocornietum perennis, Cistancho phelypaeae-Sarcocornietum pruinosae, and Halimiono portulacoidis-Sarcocornietum alpini). Our research comprises 70 relevés, which reveal distinct zonation patterns among these species in relation to their proximity to water and tidal influences. This investigation contributes to a deeper understanding of halophyte biodiversity and provides comprehensive floristic inventories, thereby facilitating future ecological assessments and restoration initiatives in fragile saline ecosystems.